Implementasi Peraturan Daerah Nomor 6 Tahun 2008 Tentang Pedagang Kaki Lima Terhadap Pembayaran Retribusi PKL di Jember - Cindy Alfin Inayah; Ahmad Junaidi (Rechtenstudent, 2020)
In fulfilling their daily needs, of course, everyone has different ways. One of them is by trading. There are many types of trade, but we often encounter street vendors (PKL). The facilities and infrastructure chosen by most of the street vendors are shoulder roads and sidewalks. This is a strategy to attract buyers who pass by in the street area. But on the other hand, it can also interfere with the convenience of road users and pedestrians. Therefore, it is for street vendors who are the attention of the local government. To help street vendors, the Regional Government of Jember Regency drafted and ratified Regional Regulation No. 6 of 2008 concerning Street Vendors. One of the points discussed in the regional regulation is the payment of levies. The purpose of this research is to read and analyze the implementation of payments from street vendors and apply it in Jember Regency. This research is qualitative research with a juridical approach and a sociological approach. Keywords: Street Vendors, Levies, Local Government.